Petrochronology applied into evaluating the tectono-metamorphic context from rocks of the Turvo-Cajati Formation, Curitiba Terrane, and its influence in the Ribeira Belt Evolution, Cajati, SP - Ricardo, Bruna da Silva (2021)
Ancient accretionary orogens occur all over the globe and their reconstruction present challenges once a great part of information is missing. The Ribeira Belt, SE Brazil, is an example of an accretionary orogen formed during the amalgamation of Gondwana in the Neoproterozoic. The current understanding of its tectonometamorphic history is a workin-progress. In this study, we focus on its southernmost part, more specifically in the Curitiba Terrane. It uses different techniques to understand the sedimentation and metamorphic settings to a metasedimentary unit, the Turvo-Cajati Formation (TCF). To evaluate the sedimentation setting, detrital zircon and probability density plots are presented. To understand the metamorphism, high precision in-situ geochronology coupled with systematic thermodynamic modelling to provide new constraints for the PT-t paths that some metasedimentary rocks have experienced. An isograd map distribution is also presented based on field work and petrography. In this unit, schists and paragneiss in distinct metamorphic conditions crop out and they are all assumed to belong to same unit (TCF). The unit is divided in three sub-units based on their metamorphic grade, the Low-TCF in the garnet zone, the Medium-TCF in the sillimanite zone and the High-TCF in the K-feldspar-kyanite/sillimanite zones with partial melting. Detrital zircon data indicates that samples from Low/Medium-TCF record signatures of a back-arc basin and the High-TCF of an accretionary wedge. It also indicates a maximum depositional age between 650-630 Ma. The metamorphism was constrained using petrography, pseudosection modelling in the MnNCKFMASHTO and NCKFMASHTO chemical systems with Perple_X software and the age of metamorphism using isotopic and chemical monazite dating. P-T phase diagrams are modelled to a broad set of samples either considering fractionation of different stages of garnet growth and conventional bulk composition. Each sample was modelled to obtain the P-T conditions from different metamorphic stages and P-T-t paths were obtained. They indicate complex evolution, even within rocks from the same metamorphic zone. Monazite ages indicate shared metamorphism in the High-TCF and Medium-TCF yielding monazite growth between 620-580 Ma, but two sample record older ages (~640 Ma). This period between 640-600 Ma anticipates our understanding of the timing of metamorphic events and that it was partially coeval with final stages of deposition. By comparing the metamorphic field gradients and P-T-t paths in High-TCF and Low and Medium-TCF, we can better understand the relation of the metamorphic events. Bimodal thermobaric ratios and pressure regime are observed by interpreting a large set of samples. Therefore, we propose a Japan-like microcontinent where the Low/MediumTCF would be in the back-arc basin and the High-TCF would be in the accretionary wedge. This microcontinent also involves a Rhyacian orthogneisses from the Atuba Complex as basement and the Piên Magmatic Arc as a result of a subduction-to-collision setting. This scenario evolved during at least 60 Ma (640-580 Ma) where the collision with the Luis Alves Microcontinent would cause most of the metamorphism and the exhumation of those rocks. Finally, somewhere around 580 Ma, the instauration of largescale shear zones and A-type granites from the Graciosa Province mark the end of those events.